Civil Society and the Democratic Peace. (January 2020) - Hegre, Håvard; Bernhard, Michael; Teorell, Jan
We theorize that three distinct structures of democratic constraint explain why more democratic dyads do not engage in military conflict with each other. We build on earlier theories that focused on electoral and horizontal accountability. We add a new dimension—the social accountability provided by an active civil society. Using several new measures from the Varieties of Democracy (V-Dem) data set, we stringently test these explanations. We find social accountability to be the strongest and most consistent predictor of nonbelligerence in dyads, that horizontal accountability is still important, but that the independent role of electoral accountability has been somewhat overstated. However, we do find that social and electoral accountability work strongly together, to make for an even greater effect. The finding is robust to a range of specifications and in the face of controls for contending theories that challenge the democratic peace (e.g., the capitalist and territorial peace theories).